2020
DOI: 10.3390/ma13092070
|View full text |Cite
|
Sign up to set email alerts
|

Novel Yttria-Stabilized Zirconium Oxide and Lithium Disilicate Coatings on Titanium Alloy Substrate for Implant Abutments and Biomedical Application

Abstract: This study aimed to create novel bioceramic coatings on a titanium alloy and evaluate their surface properties in comparison with conventional prosthetic materials. The highly polished titanium alloy Ti6Al4V (Ti) was used as a substrate for yttria-stabilized zirconium oxide (3YSZ) and lithium disilicate (LS2) coatings. They were generated using sol-gel strategies. In comparison, highly polished surfaces of Ti, yttria-stabilized zirconium oxide (ZrO2), polyether ether ketone (PEEK) composite, and poly(methyl me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…From the clinical point of view, the choice of accurately polished titanium or zirconium could be promising surface at the gingival level. The relevance of surface treatment was established in other studies with gingival fibroblasts [56].…”
Section: Discussionmentioning
confidence: 99%
“…From the clinical point of view, the choice of accurately polished titanium or zirconium could be promising surface at the gingival level. The relevance of surface treatment was established in other studies with gingival fibroblasts [56].…”
Section: Discussionmentioning
confidence: 99%
“…To further improve the material’s longevity, thus preventing peri-implantitis, one of the significant strategies focuses on avoiding bacterial adhesion on dental implant material [ 1 , 31 , 32 , 33 ]. Although complete prevention of bacterial adhesion on biomaterials is complicated, various efforts have been developed to effectively minimize and control the bacterial adhesion on biomaterial surfaces [ 15 , 20 , 33 , 34 ]. In this way, new coatings have been developed on the surface of titanium to decrease the biofilm [ 6 , 7 , 15 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…To further improve the material’s longevity, thus preventing peri-implantitis, one of the significant strategies focuses on minimizing bacterial adhesion on the dental implant material. Although complete prevention of bacterial adhesion on biomaterials is complicated, various efforts, such as fabricating thin anti-bacterial films or coatings, have been developed to effectively minimize and control the bacterial adhesion biomaterial surface [ 27 , 28 ]. Camargo et al [ 29 ] demonstrated that coatings based on SiC and TiN applied on Ti surfaces were effective against P. gingivalis in vitro.…”
Section: Discussionmentioning
confidence: 99%